The application of group investigation learning model to increase student’s study interest (Research, Society and Development, 2020)
Group investigation has function to help teacher linked between materials taught in class with students’life condition. Group investigation also pushed students to relate the relation between the lesson and the real condition. The objective of this study is to increase students’ learning outcomes in economics through the application of group investigation learning model by using both quantitative and qualitative methodology. The subject of the study is students of High School 1 Bandar, Simalungun in 11th grade of social department. These students are given pretest and posttestin two assessments cycle to see the enhancement on their study interest. Pretest is given to see students’ ability before the new learning model is implemented, while posttest is used to know the success from using the new method. The result showed that group investigation learning model can enhance the economics learning activities and outcomes. The increased number of active students during the economic lesson using group investigation model proved that it is effective to enhance students’ study ability and interest.